ANALISIS PENYEBAB PERKAWINAN MUDA (STUDI KASUS DI DESA NANGA TAMAN KABUPATEN SEKADAU) - Kurniawan, Bayu; Zakso, Amrazi; Ulfa, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThis study aimed to determine the cause of child marriage cases in Nanga Nanga Subdistrict Amusement Parks Sekadau. This research method using descriptive qualitative. This research data sources parents who have children under age married and married adolescent minors. Through observation, interviews and documentation. With manual data collection tools of observation, interview guides. The results of this study indicate that the causes of early marriage in the village of Nanga Taman twofold. Factors promiscuity, economic factors and the impact of early marriage. Factors promiscuity because of his lack of parental supervision of children let the children are free to do anything. As it happens teenagers who often come out the evening until late at night. Berduan, dating in a quiet and dark at night and also follow the event or the local party to get drunk because the booze. Not looking young men and women. Economic factors that cause early marriage because of difficulties in the economy. Parents were only farmers and noreh rubber to the low income so that the income is not sufficient for the necessities of life. From there the adolescent girls into marriage a young age to a man who established the economic choice his parents well. Accompanied support from parents and the wishes of his daughters also because they want to reduce the burden on parents whose economic difficulties. The impact of child marriage is divorce is happening because of the young age unstable emotions often lead to bickering husband and wife in the household and the incompatibility of the couple and eventually decided to divorce / separation.Keywords: early marriage, Nanga Taman